Analisis Hubungan Kesesuaian Tema Debat dengan Personal Qualities dalam Debat Calon Gubernur dan Calon Wakil Gubernur Kalimantan Barat (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the relationship between the suitability of the debate theme and the personal qualities of the candidates in the 2025 West Kalimantan gubernatorial and deputy governor debates. Using a quantitative approach and content analysis method, data was obtained from the debate transcript which was then encoded based on the level of relevance of the theme and indicators of personal qualities. The chi-square test is used to measure the relationships between variables. The results of the study show that there is a significant relationship between the suitability of the theme and the public perception of the candidate's personal qualities. Debate themes that are relevant to the candidate's background or experience tend to reinforce judgments of qualities such as empathy, integrity, and communication skills. These findings emphasize the importance of planning appropriate debate themes to showcase the candidate's leadership qualities more authentically and credibly in front of the public.